2022
DOI: 10.3390/molecules27206824
|View full text |Cite
|
Sign up to set email alerts
|

The Optimal Axis-Symmetrical Plasma Potential Distribution for Plasma Mass Separation

Abstract: The mass separation of chemical element mixtures is a relevant task for numerous applications in the nuclear power industry. One of the promising approaches to solve this problem is plasma mass separation. In a recent study, the efficiency of plasma mass separation in a configuration with a potential well and a homogeneous magnetic field was experimentally demonstrated. This article examines the possibility of increasing the distance between the deposition regions of charged particles with different masses by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Another way is to change the shape of the spatial distribution of plasma potential, so as to reduce the sensitivity of the separated particle trajectories to fluctuations. For example, in the [9], it has been shown that the most sensitive area of the trajectories are the pericentral regions. This is part of the trajectory closest to the axis of the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another way is to change the shape of the spatial distribution of plasma potential, so as to reduce the sensitivity of the separated particle trajectories to fluctuations. For example, in the [9], it has been shown that the most sensitive area of the trajectories are the pericentral regions. This is part of the trajectory closest to the axis of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma separation methods, despite a long history of development [1][2][3][4], have recently attracted much interest [5][6][7][8][9][10][11]. There are three main applications of plasma separation: reprocessing of spent nuclear fuel [12][13][14], reprocessing of radioactive waste [15,16], and recycling of rare earth elements [8].…”
Section: Introductionmentioning
confidence: 99%